Integration between the face and the mandible of Pongo and the evolution of the craniofacial morphology of orangutans. Issue 3 (14th July 2015) - Neaux, Dimitri; Gilissen, Emmanuel; Coudyzer, Walter; Guy, Franck
ABSTRACT Objectives Extant Pongo diverges from other hominids by a series of craniofacial morphological features, such as a concave face, a reduced supraorbital torus, or an upwardly orientated palate. These traits are not independent because the skull is a complex integrated structure. The aim of this study is to describe the relationship between the face and mandible of Pongo, in order to examine the link between mandibular structures and the set‐up of the unique facial features of orangutans. Materials and methods Using 3D geometric morphometrics, the morphological integration between face and mandible of Pongo is compared to that of the three extant hominids: Homo, Pan, and Gorilla. Pooled within‐species partial least squares analyses are computed in order to quantify the patterns and levels of integration. Results The covariation analyses show unique patterns of integration and levels of correlation in Pongo when compared to other hominids. This study shows that the craniofacial features distinguishing Pongo from African great apes are related to differences in the patterns of integration and levels of correlation between facial and mandibular shape. Discussion Changes in important functions may play a part in these modifications of craniofacial integration. This study underlines the importance of the mandible and of the mandibular functions in the development of the unique craniofacial features of Pongo. Am J Phys Anthropol 158:475–486, 2015. © 2015 Wiley Periodicals, Inc.